BUILDING AN IN-HOUSE MATLAB-BASED SOFTWARE FOR GRAPHICAL ANALYSIS OF FTICR MS DATA OF RIVER WATER - Thanh, Nguyen Dac; Hong Nhung, Nguyen Thi; Miyazato, Akio; Quang, Ngo Van; Tam, Nguyen Quang; Tai, Nguyen Tien (Vietnam Journal of Science and Technology, 2015)
Abstract: Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) is becoming an efficiently tool for characterization of dissolved organic matter (DOM) at the molecular level. FTICR MS data of DOM samples often involve thousands m/z peaks, therefore, visual presentation for extracting structural information from the complicated data are challenge. MATLAB (Matrix Laboratory) is a high-level language and interactive environment for visualizing and analyzing complete data. An in-house Matlab-based software for graphical presentation of the Kendrick and the van Krevelen diagrams, which are popular tools for analysis of FTICR MS data of mixture samples, is built and applied for graphical analysis of two DOM water samples from Suwannee river (USA) and Cuakhau lake (Northern Vietnam) as demonstration examples. With this software, complicated FTICR MS data of DOM samples can be visualized in a way that allows identifying DOM type and possible reaction pathways. This in-house user friendly software can be also easy to upgrade with more image diagrams as well as histograms.